Evaluación preliminar de técnicas de crioconservación en una accesión de Solanum phureja - Villa, A.L.; Sánchez, A.M.; Valbuena, R.I.; Escobar Pérez, Roosevelt H. (2007)
The Tibaitatá Research Center of Corpoica is the repository of the main Colombian potato germplasm collection with 1098 accessions, 151 belonging to Solanum phureja (98 preserved in vitro and 53 in the field), a key species because it posses resistant genes against Phytophtora infestans and because it is an important food resource for the Colombian population. There crioconservation methods are evaluated to determine the best conservation practices. For this purpose, encapsulation-dehydration and encapsulation- vitrification techniques were evaluated as reported for the Solanum species, adjusting methodologies and paying especial attention to tissue selection and quality, propagation media, apex encapsulation, concentration and time exposure to sucrose, dehydration in silica gel, and the effect of charger and PVS2 and PVS4 solutions, previous to freezing. Results indicated that explant quality and recuperation media determined the success in the crioconservation process. A preconditioning M&S medium supplemented with 0.18 µM of BAP and 0.28 µM of GA3 during 3 to 5 days allowed for tissue quality improvement after excision. Furthermore, alginate supplemented with 0.004 mg·L -1 of BAP and 0.04 mg·L -1 of GA 3 positively enhanced the response of shoot tips during steps previous to freezing. Of importance in this study, Solanum phureja is highly susceptible to physical and chemical stress, and the reason why after freezing the recovery rate was only 10%.